Learning Styles and Culture - Halil KAMIŞLI (Elementary Education Online, 2023)
The study was designed as a survey model to determine the learning styles of university preparatory class students. The study group consisted of 200 students (N: 100 Libyan- N: 100 Turkish Cypriots) attending university preparatory classes. Grasha-Reichman Learning Styles Scale was used in the research. The scale was prepared in 5-point likert form and consisted of 60 items. The scale has six subdimensions (Independent, Dependent Participant, Avoidant, Collaborative, Competitive). In order to determine whether there is a meaningful difference between learning style preferences of Turkish students and learning style preferences of Libya students, t-Test has been applied. While the significance levels of the differences between the means were tested, the error margin was accepted as p <.05 in all analyzes. As a result of the research, it was concluded that the culture influenced the learning styles.